PENGARUH PENGGUNAAN GADGET TERHADAP KARAKTER SISWA KELAS 4 SDN DEMANGAN 1 BANGKALAN - NOVITASARI, IRMA APRILIA (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This study aims to determine the effect of the use of gadgets on the characters of students at SDN Demangan 1 Bangkalan. It can be seen how the effect of using gadgets both on behavior or attitudes, social interaction or student achievement at school. This type of research is qualitative research. Data collection uses interviews and observations with informants in the field to obtain the required data. The results of the study show some of the effects of using gadgets like being individual, lazy, often emotional, and negligent about their obligations because the effects of gadget addiction.